2004
DOI: 10.1140/epjb/e2004-00374-7
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and magnetic properties of RMnX (R = Mg, Ca, Sr, Ba, Y; X = Si, Ge) studied by KKR method

Abstract: Electronic structure and magnetic properties of RMnX (R = Mg, Ca, Sr, Ba, Y; X= Si, Ge) studied by KKR method

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…According to DFT studies [142,223,[251][252][253], the AFM configuration is in general more energetically stable in MLI compounds, which is verified experimentally, with spins of Mn planes oriented anti-parallel to each other, while atomic layers can also orient anti-parallel or not. Anyway, it is also observed that the spin coupling between layers is very weak compared to the intra-layer coupling.…”
Section: Compoundsmentioning
confidence: 68%
See 1 more Smart Citation
“…According to DFT studies [142,223,[251][252][253], the AFM configuration is in general more energetically stable in MLI compounds, which is verified experimentally, with spins of Mn planes oriented anti-parallel to each other, while atomic layers can also orient anti-parallel or not. Anyway, it is also observed that the spin coupling between layers is very weak compared to the intra-layer coupling.…”
Section: Compoundsmentioning
confidence: 68%
“…This also occurs in many MnMX compounds (M = metallic elements of s, p, d or fblocks and X = elements of carbon and nitrogen groups of the periodic table) that consists in Mn layers that can couple either ferromagnetically or antiferromagnetically. Whatever the nature of M atoms, a similar number of electrons occupy d orbitals (about 5.6 electrons per Mn) and Mn-X interatomic distances responsible for the strength of the p-d hybridization and amplitude of wave functions on Mn-sites, have a crucial effect on these quasi-2D magnetic structures [142]. Hence, intermetallic compounds with square-lattice planes of Mn atoms, stabilized by other elements with mirror planes, have electronic band structures constituted by a nodal line forming a set of narrow and open cylindrical Fermi surfaces that extend along the c-axis [141].…”
Section: Room-temperature (Rt) Magnetic 2d Materialsmentioning
confidence: 99%